Tinjauan Hukum Islam, HAM dan Konstitusi terhadap Perkawinan Beda Kasta di Masyarakat Adat Ammatoa - Amir, Rudianto; Kurniati, Kurniati; Misbahuddin, Misbahuddin (Universitas Islam DDI AG.H. Abdurrahman Ambo Dalle, 2026)
This study examines the prohibition of inter-caste marriage in the indigenous community of Ammatoa Kajang in Bulukumba, South Sulawesi, from Islamic law, human rights (HAM), and the Indonesian constitutional perspectives. Rooted in pasang ri Kajang, this tradition emphasizes lineage purity and social honor, but often results in discrimination against noble women (puang) marrying men from lower classes (ata). Using descriptive qualitative methods, the study reveals tensions between exclusive customary norms and egalitarian principles in Islamic and constitutional law. Findings highlight the need to revitalize Ammatoa customary law to preserve cultural identity while aligning it with justice, equality, and respect for fundamental human rights. This study contributes significantly to legal pluralism discourse, protection of individual rights, and cultural respect within national law development.